Surface Modification Technology of Biomedical Metals - Wang, Liqiang; Xie, Lechun; Djavanroodi, Faramarz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Biomaterials are natural or artificial materials used to manufacture implants to replace lost or diseased biological structures in order to restore form and function. Biomaterials that require long-term service, such as orthopedic implants, need good physical and chemical stability, such as stainless steel and titanium alloys. The application of metal in biomedicine is becoming more and more common, but due to its various limitations, it is often necessary to modify its surface to obtain better performance and better clinical application. There are many technologies for the surface modification of medical metals, such as laser surface modification, chemical treatment, plasma surface modification, etc., and these technologies are still being developed to meet market demand. This reprint will provide important contributions related to the announced topics, focusing on biomedical metals and the surface modification technologies of biomedical metals.